1992
DOI: 10.1007/bf01232646
|View full text |Cite
|
Sign up to set email alerts
|

Propionate metabolism in cultured human cells after overexpression of recombinant methylmalonyl CoA mutase: Implications for somatic gene therapy

Abstract: Strategies for somatic gene therapy must consider the metabolic consequences of expressing the recombinant gene product in addition to methods for gene transfer and expression. We describe studies of propionate metabolism in cultured cells transfected with methylmalonyl CoA mutase (MCM), the enzyme deficient in mut methylmalonic acidemia. Transfection of MCM into mut fibroblasts restores propionate metabolism to normal levels in a dose-dependent manner. Overexpression of MCM, or the addition of excess propiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Other authors have demonstrated that hepatocytes possess an increased basal capacity for propionate metabolism[23,35] as our results also suggest. Furthermore, when individual murine tissues were examined for methylmalonyl-CoA mutase activity, the liver possessed a large amount of active enzyme, with an total activity of > 1400 nmol succinate formed/h per mg of protein[31].…”
Section: Discussionsupporting
confidence: 89%
“…Other authors have demonstrated that hepatocytes possess an increased basal capacity for propionate metabolism[23,35] as our results also suggest. Furthermore, when individual murine tissues were examined for methylmalonyl-CoA mutase activity, the liver possessed a large amount of active enzyme, with an total activity of > 1400 nmol succinate formed/h per mg of protein[31].…”
Section: Discussionsupporting
confidence: 89%
“…In sheep and rats, the highest levels of MCM activity were reported in the kidney and liver followed by brain, intestinal mucosa and skeletal muscle [4][5][6]51]. Our [21,26], and that overexpression of MCM in fibroblasts and hepatoma cells does not increase propionate flux above normal [33].…”
Section: Holoenzymementioning
confidence: 88%
“…Promoter activity was assessed by counting the number of X-gal-stained cells in ten random high-power fields from triplicate samples. Electroporation efficiency did not vary significantly in replicate control experiments performed simultaneously with identical conditions [26,33]. The number of cells exhibiting visible X-gal staining reflects the fraction of cells with expression above the threshold of visual detection and is a valid screening test for the level of gene expression.…”
Section: Promoter Activity In Transfected Cellsmentioning
confidence: 95%
“…The studies described here prove that virus-mediated rescue of neonatal lethality in Mut Ϫ/Ϫ mice, and by extension, other lethal organic acidemia murine models, can be successfully accomplished. These results are surprising when the pleiotropic nature of the enzyme defect in MMA is considered (Wilkemeyer et al, 1993) and suggest that metabolic cooperativity of propionate metabolism (Wilkemeyer et al, 1992;Stankovics and Ledley, 1993) may contribute to the biological effects observed by transient restoration of metabolism in the hepatocyte. The rapidity and severity of symptom onset in this model differ when compared with other inborn error of metabolism models that have been treated successfully with integration viruses and transposons as gene delivery agents to achieve permanent correction, such as lysosomal storage disorders (Ponder et al, 2002), aminoacidopathies (Chen and Woo, 2005), and bilirubin metabolic defects (Nguyen et al, 2005).…”
Section: Discussionmentioning
confidence: 84%